2014
DOI: 10.1155/2014/690853
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin 17 Levels in Patients with Crohn’s Disease: Real Life Data

Abstract: The aim of this study was to investigate serum IL17 levels in patients with Crohn's disease (CD) and to investigate the relationship between serum IL17 levels with disease activity. Methods. Fifty patients with CD and sex- and age-matched 40 healthy controls were included in the study. The serum IL17 levels, complete blood count, blood chemistry, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) levels were measured, and Crohn's disease activity was calculated using Crohn's disease activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…In the study by Sahin et al no difference was noted in the IL-17 concentration between patients with CD and healthy people. Furthermore, no difference was noted between the patients with active CD and patients with inactive CD [45]. Schwarzmaier et al, in a study assessing the peripheral functions of monocytes, found that the expression and IL-17 release, as compared to other proinflammatory expression and cytokines released, did not differ between non-active CD patients and healthy people from the control group [46].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the study by Sahin et al no difference was noted in the IL-17 concentration between patients with CD and healthy people. Furthermore, no difference was noted between the patients with active CD and patients with inactive CD [45]. Schwarzmaier et al, in a study assessing the peripheral functions of monocytes, found that the expression and IL-17 release, as compared to other proinflammatory expression and cytokines released, did not differ between non-active CD patients and healthy people from the control group [46].…”
Section: Discussionmentioning
confidence: 96%
“…Further studies are needed with serial IL-17 measurements for evaluation of serum IL-17 as a disease-monitoring marker. Moreover, studies should be conducted on larger groups to evaluate serum IL-17 levels in patients with severely active IBD as compared to those in healthy subjects [45].…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 24 ] It has also been shown that the expression of inflammatory mediators such as Th17 and IL-17 is significantly increased in the histopathological tissue sections obtained from patients with Crohn's disease and that these inflammatory biomarkers are associated with the activity of Crohn's disease. [ 25 26 27 ] Similarly, Kristensen et al . [ 7 ] observed an increased expression of IL-17 in patients with autoimmune thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 For instance, IL-17 expression, the number of Th17 cells, and serum IL-17 levels were increased in UV and CD patients. [11][12][13] IL-17A-deficient and IL-17 receptor-knockout mice were protected against colonic inflammation in dextran sodium sulfate (DSS)-induced colitis and trinitrobenzenesulfonic acid-induced colitis models, respectively. 14,15 Forkhead box P3 (Foxp3)-expressing T regulatory (Treg) cells play a critical role in maintaining immune homeostasis and controlling excessive inflammatory responses in the innate and adaptive immune systems.…”
Section: Introductionmentioning
confidence: 99%